(untitled) (Iraqi Journal of Medical Sciences, 2020)
Background: Febrile seizures are prevalent in children aged between 6 months and 5 years with an incidence of 2-5%. Iron deficiency is the most common hematologic disease of infancy and childhood with a period of incidence that coincides with the time of febrile seizures. Although the most common manifestation of iron deficiency is anemia, it is frequently the source of a neurologic disorders in pediatrics, including developmental delay, seizure, stroke, breath-holding episodes, pseudo tumor cerebri, and cranial nerve palsies. Objective: To investigate the association between iron deficiency and febrile seizures. Methods: Two groups (80 for each) of 6 months to 5 years old febrile children were subjected to the study between 1st of Oct. 2017 to 1st of Oct. 2018. The first group, cases, included children with febrile seizures admitted to the Pediatric Ward in Al-Imamein Al-Kadhimein Medical City, whereas the control group, included febrile children, visited the hospital during the same period for febrile illness. History was taken, physical examination was done. Blood count indices, serum iron, total iron binding capacity and serum ferritin were estimated. Lumber puncture was done in some of the patients. Statistical Analysis was done using t-test and Chi-square test (x2), P-value was considered significant if less than 0.05. Percentages and Odds ratio were estimated. A prevalence of 20-25% among cases is considered clinically relevant. Results: Both groups were comparable for age and gender (17.5±8.81) and (17.6±8.54) months, male: female ratio was (1.75:1 and 1.2:1). Family history of febrile seizure were seen in 25% and 13.75% respectively. Simple febrile seizure was found in (72.5%). The blood indices were lower in patients than the control group and statistically have significant difference in hemoglobin, hematocrit, mean corpuscular volume, serum iron and serum ferritin level with a P-value less than 0.05. A total of 36 (45%) of the cases had iron deficiency, compared to 12 (15 %) of control respectively with P-value less than 0.05. Conclusion: Iron deficiency was more frequent among children with febrile seizure than those with febrile illness alone. The results suggest that iron deficiency may be a risk factor for febrile seizure. Keywords: Febrile seizure, infants, children, iron deficiency anemia Citation: Shaheed AH, Abbas SA. The association between iron deficiency and febrile seizures in children below 5 years. Iraqi JMS. 2020; 18(2): 110-116. doi: 10.22578/IJMS.18.2.4